Meta-Analysis: The Effect of Word Search, Wordwall, Crossword, & Scramble Games in Learning English Vocabulary - Baiq Siti Humaeratul Azizah; Hidayati; Irwandi; Edi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Games are one way to make learning vocabulary fun, especially with attractive games such as Word search, Wordwall, Crossword, and Scramble. By using the meta-analysis research aimed at reviewing the effect of word search games, wordwall, crossword, and scramble games to improve student vocabulary. The results of the research observed as much as 54 eligible data with the number of participants (N), F-count, t-count and r-count. Data analysis conducted with JASP software simulation shows that the effect of Word Search, Wordwall, Crossword, and Scramble for vocabulary learning is 83% significant, that is in the high category. Based on the Forest Plot, Crosswords have the highest influence value of 1.04% more than word search, wordwall, and scramble this indicate that Crossword games are more effective in learning vocabulary. Subsequently, viewed from the variety of participants, participants with less than (40) have the highest effect with an estimate value of (1.009). The results of this research provide strong evidence regarding the effect of the games in improve students' vocabulary learning. The practical use of these findings can be maximized by educators and adopt policies in designing more effective learning to improve students' vocabulary in learning English.